2011
DOI: 10.1007/s11606-011-1651-7
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Risk Profiling: Attitudes and Use in Personal and Clinical Care of Primary Care Physicians Who Offer Risk Profiling

Abstract: BACKGROUND: Genomic risk profiling involves the analysis of genetic variations linked through statistical associations to a range of disease states. There is considerable controversy as to how, and even whether, to incorporate these tests into routine medical care. OBJECTIVE: To assess physician attitudes and uptake of genomic risk profiling among an 'early adopter' practice group. DESIGN: We surveyed members of MDVIP, a national group of primary care physicians (PCPs), currently offering genomic risk profilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
95
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 38 publications
6
95
1
Order By: Relevance
“…Participants in the present study indicated a similar expectation that health care professionals across the board will be engaged in the implementation of many types of PM applications, especially in the preventive medicine context. Confidence with genetic and genomic information was expected and has been shown to be important in this respect; a recent survey indicated that general practitioners who felt well-informed about genetics were over 10 times more likely to order a genomic risk profile (Haga et al 2011). Educational interventions can improve physician knowledge of genetics and reported confidence in the management of individuals with genetic conditions (Carroll et al 2009(Carroll et al , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in the present study indicated a similar expectation that health care professionals across the board will be engaged in the implementation of many types of PM applications, especially in the preventive medicine context. Confidence with genetic and genomic information was expected and has been shown to be important in this respect; a recent survey indicated that general practitioners who felt well-informed about genetics were over 10 times more likely to order a genomic risk profile (Haga et al 2011). Educational interventions can improve physician knowledge of genetics and reported confidence in the management of individuals with genetic conditions (Carroll et al 2009(Carroll et al , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…e importance of education in the application of pharmacogenetics has been described (19), but at present there are no broad initiatives to orchestrate genetics and genomics education of medical professionals, trainees, and the public at large. Basic genomic literacy is critical for patients, physicians, and communities if these groups are to engage in the translational research and clinical studies that are required to bring about a change in health care paradigms (20). In addition, providers should be well versed in the role of social determinants of health and the importance of cra ing care plans that take into account a patient's personal circumstances.…”
Section: Education: Professionals and The Publicmentioning
confidence: 99%
“…1 But the road to achieving those goals presents various challenges. 2 Although there are now a plethora of tests that can identify the existence of specific genes that confer increased risk of disease, for example, scientists do not yet have the ability to make accurate predictions about the likelihood that these genes will lead to particular diseases. In addition to the scientific challenges, there are a variety of unresolved policy questions.…”
mentioning
confidence: 99%